2011
DOI: 10.4028/www.scientific.net/amm.121-126.3092
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Starting Process Driven by Accumulator of a Hydraulic Free Piston Engine

Abstract: Starting system plays an important role in a hydraulic free piston engine (HFPE) and hydraulic accumulator/directional control valve combination is often employed. In this paper, the starting process of a typical starting system composed of a hydraulic bladder accumulator is firstly described, and then the mathematical model of the starting system is established and analyzed as well as some special situations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Actually, the HFPE descends from the free-piston engine and carries it forward. It is synthesized by an internal combustion engine, hydraulic technology and electronic control technology [6]. HFPE development roughly experienced the following stages: (1) Initial stage (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990) Figure 2 shows a hydraulic free-piston which uses a two-stroke reflux scavenging scheme: its load is hydraulic oil with a certain pressure; a hydraulic accumulator is applied as the energy storage component [7].…”
Section: The History Of Hfpesmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the HFPE descends from the free-piston engine and carries it forward. It is synthesized by an internal combustion engine, hydraulic technology and electronic control technology [6]. HFPE development roughly experienced the following stages: (1) Initial stage (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990) Figure 2 shows a hydraulic free-piston which uses a two-stroke reflux scavenging scheme: its load is hydraulic oil with a certain pressure; a hydraulic accumulator is applied as the energy storage component [7].…”
Section: The History Of Hfpesmentioning
confidence: 99%
“…Energies 2021, 14, x FOR PEER REVIEW 3 of 23 (a) The combination of engine and hydraulic pump (b) The hydraulic free-piston engine Figure 1. The different structures of a conventional engine and an HFPE [6].…”
Section: The History Of Hfpesmentioning
confidence: 99%
“…Xia and Zhou of Zhejiang University studied DHFPE and focused on the energy distribution, control of the compression ratio, and the vibration of the piston. The results showed that the vibration of the piston was a self-excited vibration and the engine was a large scope stability system [9][10][11]. Zhao and Yuan of Beijing Institute of Technology also developed an SHFPE and utilized the uniflow scavenge to improve the scavenge ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The SHFPE belongs to single-cylinder diesel engine and has an imbalance structure, so the alternant forces of the compression accumulator and the released heat of the injected fuel acting on the FPA lead the engine body to vibrate. Generally, the engine body is mounted to the base by the bolts with some vibration absorptions [6,7] . The body vibration can also be eliminated through putting several engine units symmetrically to get a balance structure [7,8] .…”
Section: Introductionmentioning
confidence: 99%